2015
DOI: 10.1021/acs.chemrestox.5b00401
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Heterocyclic Amines 2-Amino-9H-pyrido[2,3-b]indole and 2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine in Urine: Effects of Cigarette Smoking

Abstract: 2-Amino-9H-pyrido[2,3-b]indole (AαC) and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) are carcinogenic heterocyclic aromatic amines (HAAs) formed during the combustion of tobacco and during the high-temperature cooking of meats. Human enzymes biotransform AαC and PhIP into reactive metabolites, which can bind to DNA and lead to mutations. We sought to understand the relative contribution of smoking and diet to the exposure of AαC and PhIP, by determining levels of AαC, its ring-oxidized conjugate 2-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
2
19
1
Order By: Relevance
“…The AαC-6-OH and AαC-3-OH reference compounds produced by human liver microsomes were characterized by 1 H-NMR, which unambiguously identified the sites of ring-oxidation of AαC. 17,34 Taken together these results lead us to identify M2 as AαC-6- O -Gluc and M3 as AαC-3- O -Gluc.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The AαC-6-OH and AαC-3-OH reference compounds produced by human liver microsomes were characterized by 1 H-NMR, which unambiguously identified the sites of ring-oxidation of AαC. 17,34 Taken together these results lead us to identify M2 as AαC-6- O -Gluc and M3 as AαC-3- O -Gluc.…”
Section: Resultsmentioning
confidence: 83%
“…16 Recently, a tobacco smoking cessation study conducted in the United States revealed that AαC was present in urine during the smoking phase in greater than 90% of the subjects, and the geometric mean urinary level of AαC decreased by 87% six weeks after cessation of tobacco usage. 17 These urinary biomarker data demonstrate that tobacco smoking is a significant source of AαC exposure. The data reported in the literature on urinary level of AαC in human is restricted to few reports where the mean level of AαC in urine of subjects who smoked greater than 20 cigarette per day range between 11.9 and 3511.9 pg/mg creatinine.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…68 The amount of AαC formed in well-done cooked meats has often not been measured and the estimates of daily exposure to AαC are uncertain; 6972 however, urinary biomarker data reveal that the exposure to AαC through tobacco smoke or well-done cooked meat can be appreciable. 7376 Our biochemical data on UGT1A9 activity offers an alternative interpretation for the association among the high/intermediate UGT1A9 genotype and colorectal cancer risk. HAA, such as AαC and PhIP, undergo N-oxidation by P450 1A2 in the liver, followed by O -glucuronidation of the N -hydroxy-HAA metabolites by UGT1A9 and transport of the HAA-HN- O -Gluc via bile to the gastrointestinal tract, where ensuing binding to colonic DNA occurs.…”
Section: Discussionmentioning
confidence: 99%